Traditional ecological knowledge about plants cultivated by fishermen at Community Estirão Comprido, Pantanal matogrossense, Brazil - Fernando Ferreira de Morais; Rodrigo Ferreira de Morais; Carolina Joana da Silva (Boletim do Museu Paraense Emílio Goeldi. Ciências Humanas, 2009)
Ethnoecological study dealing with Traditional Ecological Knowledge (TEK) on plants cultivated by fishermen at Community Estirão Comprido, Cuiabá River, Barão de Melgaço, Pantanal matogrossense, Brazil. Twenty two fishermen were interviewed to elaborate a free list on the plants. The list was analyzed through: Smith’s salience index, cultural consensus analysis, similarity and dissimilarity with multidimensional scaling, and stacking technique. The software ANTHROPAC 4.0 was used for the data statistical treatment. Based on the Smith’s salience index, we identified six ruptures in the cultural domain of cultivated plants, concentrating on 116 ethnospecies. Orange and maize were most frequently cited and ranked first in the free list; they are in the first rupture of the free list with Smith index of 0.728 and 0.711, respectively. The culturalconsensus analysis indicated that TEK on cultivated plants characterizes a consensus and concentrates on 18 ethnospecies. Stacking analysis evidenced that knowledge on plants is related to their different usage types. In this context, the usage and management possibilities emphasized in the present study can contribute to the development of public polices for conserving the ecological and cultural biodiversity.